Comparison of Muscle Recruitment Patterns During Sit-to-Stand and Stand-to-Sit in "Movement System Impairment" Subgroups of Low Back Pain and Healthy Women - Neda Orakifar; Mohammad Jafar Shaterzadeh-Yazdi; Reza Salehi; Mohammad Mehravar; Neda Namnik (Shiraz University of Medical Sciences, 2018)
Background: While various studies have examined motor control differences between subjects with and without low back pain (LBP), only a few have investigated the muscle recruitment pattern in classified LBP patients during functional activity. The aim of this study was to investigate the firing pattern of the main muscles involved in sit-to-stand (STD) and stand-to-sit (STS) tasks in two prevalent LBP subgroups based on movement system impairment (MSI) classification. Methods: A total of 37 women between 18 and 50 years of age voluntarily participated in this cross-sectional study. They were divided into three groups (15 healthy, 15 lumbar extension rotation syndrome (LERS), and seven lumbar flexion rotation syndrome (LFRS)). Surface electromyography was recorded bilaterally from the trunk stabilizer muscles-i.e. the internal oblique (IO), lumbar erector spine (ES), and hip mobilizer muscles-and the medial (MH) and lateral (LH) hamstring muscles during STD and STS tasks. The variations in EMG onset muscle timing and asymmetry in side-to-side muscle timing were measured. Results: The firing sequence during the STD task showed no significant difference among groups. However, in the healthy and LFR groups the trunk stabilizer muscles were activated before the hip mobilizer muscles, and in the LERS group an insignificant delay was shown in the onset of the ES activity. There was no significant difference of bilateral muscle timing during STD. In the STS task no consistent order of pattern was found even in the healthy group. The bilateral muscle timing of IO (mean difference, -427.00; P=0.021) and ES (mean difference, 1964.57; P=0.000) had significant difference in the LFRS group during STS. Conclusion: The cumulative effects of recruitment pattern impairment may contribute to continuing the cycle of lumbar movement impairments and subsequent persistence of LBP.